Effect of NPS and Zinc Fertilizer Rates on Growth and Yield of Onion (Allium cepa L.) at Shewa Robit, North Shewa, Ethiopia - Kelem Muluneh; Tiru Tesfa; Bizuayehu Desta (Applied and Environmental Soil Science)
Onions, a crucial bulb crop cultivated globally, including in Ethiopia, face significant production challenges. These constraints encompass poor soil fertility, inappropriate fertilizer usage, limited availability of improved varieties, disease and insect pests, and the high costs associated with commercial fertilizers. Among these limitations, improper fertilizer application amounts and types play a pivotal role in restricting onion production. To address this, a field experiment was conducted during the 2020-2021 cropping season in the Shewa Robit district of the North Shewa zone. The study assessed the impact of NPS and Zn fertilizer rates on onion growth and yield. The treatments included four NPS fertilizer rates (0, 121, 242, and 363 kg/ha) and four levels of ZnSO4 (0, 0.25, 0.5, and 0.75% w/v). The experiment was laid out as a randomized complete block design in a factorial arrangement and replicated three times. The results demonstrated that the interaction effect of NPS and Zn fertilizers significantly influenced various onion parameters, including days to maturity, plant height, leaf length, marketable bulb yield, unmarketable bulb yield, and total bulb yield. The application of NPS at a rate of 242 kg/ha and 0.75% ZnSO4 led to the highest plant height (65.20 cm), leaf length (51.93 cm), marketable bulb yield (34.87 t/ha), and total bulb yield (35.04 t/ha). In addition, this treatment combination yielded the highest net benefit (908,628.89 ETB/ha) with an acceptable MRR (313.64%) compared to other treatments. Hence, it can be recommended for economical production of onion in the study area and areas with similar agroecologies.